To Provide Higher Education Students with an Understanding of the History and Place of the Advanced Afghan Rubab - Bakhtiyar Ergashbayev Mirzamaxmudovich (International Journal on Integrated Education, 2021)
Afghan rubab is widespread among the Uzbek and Tajik peoples in countries such as Afghanistan, India, Pakistan, Egypt, China, as well as in Central Asia. It is loved in the Fergana Valley, and it is difficult to determine where the Afghan rubab came from, as it is described differently in different sources. In this article, the author provides students with insights into the history and origins of the advanced «Afghan rubab»based on sources.